2021
DOI: 10.24018/ejmed.2020.2.6.612
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Stress and Food Consumption Frequency among Medical Students of Rawalpindi Medical University, Pakistan

Abstract: Stress is a common health problem among medical students. Higher stress among students leads to change in food preference. This study was aimed to assess the relationship between perceived stress and food pattern among final-year MBBS student of Rawalpindi Medical University. This cross descriptive cross-sectional study was conducted among final-year MBBS students of Rawalpindi Medical University in January 2020.Data was collected through Perceived stress scale and self-structured questionnaire about demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
(32 reference statements)
1
5
0
Order By: Relevance
“…Various reasons have been manifested in literature, that leads to higher consumption of junk food among people in contrast to healthy foods. These reasons include taste, easy digestion, mental disease and easy availability [12], [13]. Higher incidence of CAD among fast food eaters could be due their higher fat content which induce damage to endothelium of blood vessels, atheroma formation in the blood vessels and eventually blockage of blood vessels which leads to ischemia and in the end necrosis of organ that get supply from that blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Various reasons have been manifested in literature, that leads to higher consumption of junk food among people in contrast to healthy foods. These reasons include taste, easy digestion, mental disease and easy availability [12], [13]. Higher incidence of CAD among fast food eaters could be due their higher fat content which induce damage to endothelium of blood vessels, atheroma formation in the blood vessels and eventually blockage of blood vessels which leads to ischemia and in the end necrosis of organ that get supply from that blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Different logics have been displayed in literature, that leads to increase consumption of fast food among people in comparison to healthy foods. These reasons include taste, easy digestion, mental disease, and easy availability [21]- [23]. Higher prevalence of HTN among junk food eaters could be due to their higher salt and fat content which make into action various systems of body and consequently leads to raised BP of both types [17], [18].…”
Section: Discussionmentioning
confidence: 99%
“…These include easy availability, easy digestion, tasty and energy enrich nature [21]. Mental diseases like stress and depression are also reported as driving factors for higher consumption of junk foods [22], [23].…”
Section: Association Of Foods With Hypertensionmentioning
confidence: 99%
“…Studies mentioned earlier covered stress and depression in medical students, but such studies were conducted in the context of the traditional educational system. [6][7][8][9][10][11] The present study is different, having been conducted to evaluate the learning environment quality after the updated MBBS curriculum was introduced. The aim of the present study was to fill in the gap regarding the effect of the curriculum change on the stress of medical students, as well as identifying the source of that stress and its impact on their quality of life.…”
Section: Introductionmentioning
confidence: 99%
“… 4 , 5 Medical students encounter many stressors during their journey to achieve their goals; 5 these include an extensive medical curriculum, information overload, long study hours, high academic and family expectations, competition, and frequent and varied examinations. 3 Several studies have reported moderate to high levels of stress among medical students in different countries worldwide, including 91.1% in India, 6 84.5% in Pakistan, 7 83.5% in Thailand, 8 and 49% in Malaysia. 9 In Saudi Arabia, stress was reported in Imam Abdulrahman Bin Faisal University, Dammam, at 67.9% in 2018, 5 in Rabigh Medical College, Jeddah, at 59.2% in 2015, 3 in Umm Al-Qura University (UQU), Makkah, at 70.9% in 2015, 10 and in King Saud University, Riyadh, at 63% in 2011.…”
Section: Introductionmentioning
confidence: 99%